Peer support work for people experiencing mental distress attending the emergency department: Exploring the potential. (7th September 2021) - Brasier, Catherine; Roennfeldt, Helena; Hamilton, Bridget; Martel, Andrew; Hill, Nicole; Stratford, Anthony; Buchanan‐Hagen, Sally; Byrne, Louise; Castle, David; Cocks, Nadine; Davidson, Larry; Brophy, Lisa
Abstract: Objective: This study explored the benefits and limitations of employing peer support workers, who utilise their own lived experience of mental distress and recovery, to support people experiencing mental distress who are attending the ED. Methods: This co‐produced qualitative study utilised four phases: (i) assemble a collaborative multi‐disciplinary research team and Expert Panel, of which at least half identified as having lived experience; (ii) a site visit to an ED; (iii) focus groups with consumers, support persons and ED staff; and (iv) a learning workshop for peer workers. Results: Focus groups were run for consumers ( n  = 7), support persons ( n  = 5) and ED staff ( n  = 7). Eleven consumer peer workers participated in the learning workshop. Four themes were identified and triangulated: the individual in distress, peer support work, a 'Peers in EDs' service and the ED context. Overall, findings suggest that peer support workers contribute important skills including listening, de‐escalation, relationship‐building and empathy. Conclusions: This study identified that peer support workers would bring important skills to an ED (e.g. empathetic support, de‐escalation). However, significant workforce and organisational support would be required.